Geochemical Analysis of Two Samples of Bitumen from Jars Discovered on Muhut and Masirah Islands (Oman) - Jacques Connan; Michael H. Engel; Robert B. Jackson; Seth Priestman; Tom Vosmer; Alex Zumberge (Separations, 2021)
Two samples of bitumen were obtained, one from a torpedo jar (c. 3rd–8th C. AD) from Masirah island and one from a Tunisian jar (c. 18th C. AD) from Muhut island off the central coast of Oman. Steranes and terpanes, as well as isotope data on chromatographic fractions, were used as tools to characterize the bitumen. Comparison of data with those already acquired on bitumen from torpedo jars from Thailand, Iran, Indonesia, Sri Lanka, Saudi Arabia, India, and oil seeps from Iran and Iraq allowed us to conclude that the bitumen originated from different areas of southwest Iran. Those of the Muhut jar were likely from Khuzistan, whereas those from Masirah island appear to have been sourced from Kermanshah. These findings are in keeping with other similar geochemical studies undertaken on bitumen lined vessels from across the region (see more below).